Mortality from trauma haemorrhage and opportunities for improvement in transfusion practice. Issue 4 (3rd February 2016) - Stanworth, S J; Davenport, R; Curry, N; Seeney, F; Eaglestone, S; Edwards, A; Martin, K; Allard, S; Woodford, M; Lecky, F E; Brohi, K
Abstract: Background: The aim of this study was to describe the prevalence, patterns of blood use and outcomes of major haemorrhage in trauma. Methods: This was a prospective observational study from 22 hospitals in the UK, including both major trauma centres and smaller trauma units. Eligible patients received at least 4 units of packed red blood cells (PRBCs) in the first 24 h of admission with activation of the massive haemorrhage protocol. Case notes, transfusion charts, blood bank records and copies of prescription/theatre charts were accessed and reviewed centrally. Study outcomes were: use of blood components, critical care during hospital stay, and mortality at 24 h, 30 days and 1 year. Data were used to estimate the national trauma haemorrhage incidence. Results: A total of 442 patients were identified during a median enrolment interval of 20 (range 7–24) months. Based on this, the national incidence of trauma haemorrhage was estimated to be 83 per million. The median age of patients in the study cohort was 38 years and 73·8 per cent were men. The incidence of major haemorrhage increased markedly in patients aged over 65 years. Thirty-six deaths within 24 h of admission occurred within the first 3 h. At 24 h, 79 patients (17·9 per cent) had died, but mortality continued to rise even after discharge. Patients who received a cumulative ratio of fresh frozen plasma to PRBCs of at least 1 : 2 had lower rates of death than those who received a lower ratio. There were delays in administration of blood. Platelets and cryoprecipitate were either not given, or transfused well after initial resuscitation. Conclusion: There is a high burden of trauma haemorrhage that affects all age groups. Research is required to understand the reasons for death after the first 24 h and barriers to timely transfusion support. Abstract : Severe delays in transfusion